P–398 Decidualization inhibits the expression of CXCR3-binding chemokines by human decidual stromal cells. Role in maternal-fetal immune tolerance. (6th August 2021) - Llorca, T; García, O; Martínez, R; Méndez, C; Ruiz, M J; Abadía, A C; Ruiz, C; García, E
Abstract: Study question: We aimed to analyze the effects of decidualization on the expression of chemokines that attract abortogenic T cells by human DSCs. Summary answer: Decidualization inhibits the expression of chemokines that attract Th1 and Tc1 cells by DSCs, thereby preventing the arrival of abortogenic T cells into the decidua. What is known already: Decidual stromal cells (DSCs) are the most abundant cells in the human decidua, the tissue that constitutes the maternal component of the placenta. Numerous evidences confirm that DSCs play a key role in maternal-fetal immune tolerance. In normal pregnancy, DSCs undergo a process of differentiation (decidualization) under the effect of progesterone and other pregnancy hormones. Decidualized DSCs become rounded and secrete prolactin, IL–15 and other factors. In the mouse, it has been observed that during pregnancy, DSCs inhibit the expression of chemokines that attract abortogenic Th1 and Tc1 cells from blood to the decidua. Study design, size, duration: We compared the expression of CXCR3-binding chemokines by undifferentiated and decidualized human DSCs. We also compared the capacity of these cells to attract activated Th1 and Tc1 cells in vitro. Ten DSC lines were obtained from elective vaginal terminations of first-trimester pregnancies (6–11 weeks). Donors were healthy women aged 20–30 years. Informed consent was obtained from each donor. This study was approved by the Research and Ethics Committee of the University of Granada. Participants/materials, setting, methods: Decidual stromal cell lines were established as previously described. These lines were decidualized with progesterone and cAMP in vitro. The expression of chemokines by these cells was studied by RT-PCR. Peripheral blood lymphocytes were activated with PHA, anti-CD28 and IL–2. As a consequence of this activation, CXCR3+ Th1 and Tc1 cells were produced. We used a migration assay in Transwell chambers to study the capacity of DSCs to attract these activated T cells. Main results and the role of chance: We observed that those chemokines that bind to CXCR3, a chemokine receptor detected in activated Th1 and Tc1 cells, were not expressed by either undifferentiated and decidualized DSCs (CXCL9) or their expression was inhibited in decidualized DSCs (CXCL10 P < 0.01, CXCL11 P < 0.05). We found that conditioned media of undifferentiated DSCs decreased the migration of CXCR3+ activated T cells (Th1 and Tc1 cells) (P < 0.05), and this effect was even stronger with conditioned media of decidialized DSCs P < 0.001). These results demonstrated that decidualization of DSCs during pregnancy inhibits the expression of chemokines that attract Th1 and Tc1 cells by DSCs, thereby preventing the arrival of abortogenic T cells into the decidua. Limitations, reasons for caution: This is an in vitro study due to the impossibility of performing an in vivo study in humans for ethical reasons. Wider implications of the findings: Several publications have shown that DSCs have a therapeutic effect in various Th1-associated diseases. Our results explain this effect and suggest the extension of the use of these cells in the treatment of this type of diseases. Trial registration number: Not applicable